KESESUAIAN HASIL SWAB MENGGUNAKAN ALAT TCM (TES CEPAT MOLEKULER) DENGAN RT-PCR SEBAGAI GOLD STANDARD DIAGNOSTIK PEMERIKSAAN LABORATORIUM COVID-19 - Pipit Sofiana; Christina Destri Wiwis Wijayanti; Halik Wijaya; Titik Sundari (Jurnal SainHealth, 2022)
Since the WHO announced the global pandemic caused by COVID-19 in February 2020, various steps have been taken to deal with it, one of which is increasing laboratory tests to support the diagnosis. This study aimed to describe the suitability of the COVID-19 swab results using the TCM (Molecular Rapid Test) tool with RT-PCR as the gold standard for diagnostic COVID-19 laboratory examinations at Dr. Wahidin Sudiro Husodo Hospital, Mojokerto City, reaching 100% or not.  This research is descriptive with a retrospective approach, taking data from the examination results in August 2020, which were carried out at the Clinical Pathology Laboratory and PCR Biomolecular Laboratory, Dr. Wahidin Sudiro Husodo Hospital Mojokerto City.  The results of the 20 samples examined using the TCM tool obtained postpositive results. In contrast,e results in as many as seven samples and 13 samples with negative results. In comparison, with the RT-PCR tool, 6 samples had positive results and 14 samples with negative results, so that 1 (5%) did not come according to the results, namely in samples with code C the results with the TCM tool showed p those with the RT-PCR tool showed negative results. Then the research results using the TCM if the percentage according to RT-PCR is 95%.  Many factors could cause this difference in results. If viewed from pre-analytic factors, it can be caused by improper sampling process, patient cooperation, poor quality of the specimen or containing only very few samples, inaccurate sample delivery and storage conditions, sample contamination, and pipetting errors during sample preparation. At the analytical stage, the presence of cross-contamination, virus mutation, or PCR reaction barriers, the quality of the reagent kit, and the skills of the analyst working on it also affect the results because the more skilled you are, the more precise and correct standard procedures can be performed.  Keywords: COVID-19, TCM (Molecular Rapid Test), RT-PCR